2002
DOI: 10.1076/icsp.9.2.121.8696
|View full text |Cite
|
Sign up to set email alerts
|

Supervision of children aged two through six years.

Abstract: Manufacturers of household products--including appliances, exercise equipment, and even some children's toys--expect consumers to supervise their children to prevent product-related injuries. This approach to hazard prevention places the burden of safety on parents and caretakers. This study examined actual supervision practices of parents of children between the ages of two and six years. 59 parents, aged 31 to 40 years, residing in Montgomery County, Maryland, completed a 24-item self-administered questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 0 publications
1
31
1
Order By: Relevance
“…The average LOS in our study is in line with data published, ranging from 1.97 [14] and 2.5 days [15] up to 3.7 days per admission. Longer LOS are commonly attributed to delayed or overlooked diagnosis [16] due to the onset of complications which usually reflect into a prolonged hospitalization.…”
Section: Discussionsupporting
confidence: 90%
“…The average LOS in our study is in line with data published, ranging from 1.97 [14] and 2.5 days [15] up to 3.7 days per admission. Longer LOS are commonly attributed to delayed or overlooked diagnosis [16] due to the onset of complications which usually reflect into a prolonged hospitalization.…”
Section: Discussionsupporting
confidence: 90%
“…Prior findings have suggested that child age affects the nature of caregiver supervision, with younger children monitored more closely (Pollack-Nelson & Drago, 2002). In this study, preschool children were highly supervised, possibly influenced by the recommendation by key water safety stakeholder RLSSA (2010) that children aged 0-4 years require close, constant, and focused supervision.…”
Section: Discussionmentioning
confidence: 77%
“…Supervision is often an assumed method of injury prevention (Pollack-Nelson & Drago, 2002); however, previous studies have indicated that a number of factors affect the level of supervision caregivers provide to children (Kendrick et al, 2007;Morrongiello, Ondejko, & Littlejohn, 2004b;Petrass et al, 2011b). In public pools, the age of the child, the age of the caregiver, the number of children for whom the caregiver was responsible, and the swimming ability of the child affected the nature of supervision and often resulted in children been placed at increased risk of unintentional injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies have direct measures of supervisory behaviors per se, parents report they believe that they less closely supervise older than younger children (Garling & Garling, 1993;Pollack-Nelson & Drago, 2002). There also is some indirect evidence to suggest that boys are less closely supervised than girls (Fagot, 1974(Fagot, , 1978Newson & Newson, 1976;Saegert & Hart, 1976); however, recent direct comparisons of home supervision revealed only one sex difference that supported this notion (Morrongiello et al, 2006b).…”
Section: Present Studymentioning
confidence: 86%